Studi Hasil Coating Ni-Al-Fe dari Kombinasi Nickel Electroplating dan Hot Dipping (Galvanizing) pada AISI 1020 - Dikky Antonius (SIMETRIS, 2019)
Usually, coating formed to obtain a protective layer which would prevent the base material contacting the air. However, currently many coating formed not only to protect the base material, but to enhance the characterization. Nickel electroplating followed by galvanizing using molten aluminum held in this experiment to obtain the Ni-Al phase to enhance the mechanical behavior of the samples. Sample was dipped into the electrolyte consist of NiSO4, NiCl2, and H3BO3 with concentration 250gr/l, 50gr/l, and 30gr/l respectively. All of them was electroplated in 20 minutes. Galvanizing with molten aluminum at 700oC was with varied in 10s, 20s and 30seconds process. The coating clearly shows 5 segment layer above the base metal: Nickel Layer, 2 layer of NiAl3, Ni-Al layer and Aluminum layer. The longer experiment sustained, the thinner nickel coating found. However, the Ni-Al phase which contributed to 1st,2nd and 3rd layer does not make any difference thickness. Moreover, there are many worm-structure Ni-Al found in the aluminum coating, showing that nickel was likely diffused in to the aluminum instead of the ferrous